Immune Response of Senegalese Sole against Betanodavirus Mutants with Modified Virulence. - Gémez Mata, Juan; Souto, Sandra; Bandin, Isabel; Alonso-Sánchez, María del Carmen; Borrego-García, Juan José; Labella Vera, Alejandro Manuel; García-Rosado, Esther (MDPI, 2021)
Nervous necrosis virus (NNV), genus Betanodavirus, the etiological agent of the viral encephalopathy and retinopathy (VER), presents a genome with two positive-sense single-stranded RNA segments. Striped jack nervous necrosis virus (SJNNV) and red-spotted grouper nervous necrosis virus (RGNNV), together with reassortants RGNNV/SJNNV, are the betanodaviruses predominantly isolated in Southern Europe. An RGNNV/SJNNV reassortant isolated from Senegalese sole (wt160) causes high mortalities in this fish species. This virus presents differences in the sequence of the 3’ non-coding region (NCR) of both segments compared to RGNNV and SJNNV reference strains. Previously, it has been reported that the reversion of two of these differences (nucleotides 1408 and 1412) in the RNA2 3’NCR to the SJNNV-type (recombinant r1408-1412) resulted in a decrease in sole mortality. In the present study, we have applied an OpenArray® to analyse the involvement of sole immune response in the virulence of several recombinants: the r1408-1412 and two recombinants, developed in the present study, harbouring mutations at positions 3073 and 3093 of RNA1 3’NCR to revert them to RGNNV-type. According to the correlation values and to the number of expressed genes, the infection with the RNA2-mutant provoked the most different immune response compared to the immune response triggered after the infection with the rest of the viruses, and the exclusive and high upregulation of genes related to the complement system. The infection with the RNA1-mutants also provoked a decrease in mortality and their replication was delayed at least 24 h compared to the wt160 replication, which could provoke the lag observed in the immune response. Furthermore, the infection with the RNA1-mutants provoked the exclusive expression of pkr and the downregulation of il17rc.
Keywords: Virus con ARN; Lenguados; Solea senegalensis; Reassortant nervous necrosis virus; Immune response